2006
DOI: 10.1002/eat.20324
|View full text |Cite
|
Sign up to set email alerts
|

Is multi-impulsive bulimia a distinct type of bulimia nervosa: Psychopathology and EMA findings

Abstract: Clinical classification of MIB was empirically supported through LCA. Although the classes failed to differ in bulimic behavior, MIB appears to represent a group of bulimic individuals with significant trauma histories and associated psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1
5

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 25 publications
5
59
1
5
Order By: Relevance
“…This association may support the existence of an eating disorder subgroup that exhibits a cluster of impulsive, problematic behaviors. Previously described as "multi-impulsive," these individuals with BN have been found to display poor response to treatment (Fichter, Quadflieg, & Rief, 1994) as well as other negative outcomes (Keel & Mitchell, 1997;Myers et al, 2006). The identification of diet pill use as another behavior that may characterize these individuals is important for further understanding the nature of eating pathology in this particularly severe subgroup of eating disorder patients.…”
Section: Discussionmentioning
confidence: 99%
“…This association may support the existence of an eating disorder subgroup that exhibits a cluster of impulsive, problematic behaviors. Previously described as "multi-impulsive," these individuals with BN have been found to display poor response to treatment (Fichter, Quadflieg, & Rief, 1994) as well as other negative outcomes (Keel & Mitchell, 1997;Myers et al, 2006). The identification of diet pill use as another behavior that may characterize these individuals is important for further understanding the nature of eating pathology in this particularly severe subgroup of eating disorder patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Prior research has been reported using latent class analysis (LCA)/latent profile analysis (LPA). Sullivan et al using LCA found little support for the thresholds used in the DSM-IV for bulimia nervosa (BN).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, nine have used LCA. [3][4][5][6][7][8][9][10][11] However, these nine studies vary considerably in terms of sample composition and analytic strategy. Two of the studies 7,9 used unique sets of indicators that were not eating disorder symptoms while two additional studies 8,10 involved community samples that included a majority of healthy subjects with minimal endorsement of symptoms; these four studies were not used in defining the true model.…”
Section: Simulating An Underlying Modelmentioning
confidence: 99%
“…These techniques have particular relevance for the field of eating disorder research, where much recent attention has focused on establishing the validity of systems for classifying eating disorders 1 and revising diagnostic criteria for DSM-5. 2 A number of studies have utilized LCA [3][4][5][6][7][8][9][10][11] or LPA [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] to identify eating disorder phenotypes. However, despite the recent popularity of these methods in the field of eating disorders, little consideration has been…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation